Potential Combination of Tinospora crispa, Andrographis paniculata, Cinnamomum burmanii, Syzygium polyanthum, and Momordica charantia Extracts Against Intake of Glucose in Muscle Rats-Induced Diabetes Mellitus - Rachmat Hidayat; Patricia Wulandari (HM Publisher, 2021)
Diabetes mellitus is a chronic condition that disturbs the body's blood sugar regulation. This disorder is characterized by a decrease in the ability of body cells to intake glucose into cells. Due to the failure of cells in glucose intake, glucose buildup occurs in the extracellular, namely in the plasma. These medicinal plants contain quite varied secondary metabolites, and these plants are rich in flavonoids, alkaloids, terpenes, and glycosides. The content of these secondary metabolite compounds is believed to be rich in antioxidant effects so that it has the effect of being able to suppress various oxidative stress conditions that cause damage to various organs due to blood sugar dysregulation. The effect of Tinospora crispa, Andrographis paniculata, Cinnamomum burmanii, Syzygium polyanthum and Momordica charantia extract on blood sugar levels and GLUT4 protein expression in muscle tissue shows the potential of the test extract's ability to improve blood glucose intake to cells so as to maintain blood sugar regulation.